The Labour of Black Love: James Cone, Womanism, and the Future of Black Men’s Theologies - Wickware, Marvin E. (Black theology, 2021)
Following James Cone’s death, Black male theologians must ask how we might properly honour his influence upon our ongoing work, while reckoning with its limits in relation to his struggle to fully appreciate womanist critiques. This article focuses on love as a central theme in Cone’s theology, engaging with Cone’s work, as well as Delores Williams’s Sisters in the Wilderness and Hortense Spillers’s “Mama’s Baby, Papa’s Maybe.” This article proposes that Cone fails to address the injustice inherent in accepting the affective labour of love as women’s work. As a disciplinary intervention, this article suggests that Black male theologians must open ourselves to being transformed and fully drawn into that labour of love. As a constructive theological argument, this article finds a point of consonance between Cone’s and Williams’s Christologies. Jesus embraced freedom guided by love, offering ministerial vision to many, rejecting imperial power on and of the cross.